PENGARUH KEADILAN, SISTEM PERPAJAKAN, DISKRIMINASI, DAN PEMAHAMAN PERPAJAKAN TERHADAP PERSEPSI TAX EVASION ( STUDI EMPIRIS WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA SEMARANG TIMUR ) - Afri Mei Saputra, 13.05.52.0107; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the influence of justice, taxation system, discrimination, and understanding taxation against tax evasion perception. The sample in this study is a corporate taxpayer registered in the East Semarang KPP. Retrieval technique using Convinience Sampling counted 98 taxpayers of agencies. Data processing using SPSS version 23 with multiple linear regression analysis techniques. Based on the results of the analysis shows understanding of taxation has a significant negative effect on the perception of tax evasion. The system of taxation, discrimination and justice is negative not significant to the tax evasion. Keywords: Understanding taxation, taxation system, discrimination, justice, tax evasion.